Boron transport simulation using the ERO2.0 code for real-time wall conditioning in the large helical device. (December 2020) - Shoji, M.; Kawamura, G.; Romazanov, J.; Kirschner, A.; Eksaeva, A.; Borodin, D.; Masuzaki, S.; Brezinsek, S.
Highlights: Impurity Powder Dropper (IPD) is introduced for wall-conditioning (boronization) in LHD. Boron transport simulation was performed using ERO2.0, EMC3-EIRENE and DUSTT. ERO2.0 reveals an optimum condition for effective wall-conditioning using the IPD. Boron supplied from the IPD is locally deposited for high density plasmas. The supplied boron is uniformly distributed toroidally for low density plasmas. Abstract: The three-dimensional Monte-Carlo impurity transport and plasma surface interaction code ERO2.0 is applied to a full-torus model for the Large Helical Device (LHD). In order to find an optimum experimental condition for effective real-time wall conditioning (boronization) using an Impurity Powder Dropper (IPD), the toroidal and poloidal distribution of the boron flux density on the divertor components and the vacuum vessel are surveyed in various experimental conditions. The source profile of the neutral boron atoms originated from boron powders supplied from the IPD is calculated using the DUSTT code in background plasmas provided by the EMC3-EIRENE code. The simulations using ERO2.0 predict that higher plasma density operation is inappropriate for the effective wall conditioning because of the toroidally localized boron flux density in a closed helical divertor region. The ERO2.0 simulations have successfully revealed an optimum experimental condition for the wall conditioning with the toroidally uniform boron flux density in the closed helical divertor region.